Satisfação corporal, comportamento alimentar e perfil nutricional de mulheres praticantes de dança em Itaqui/RS - (:unkn) unknown (Universidade Federal do Pampa, 2013)
To evaluate the level of body satisfaction, eating habits and nutritional status of women aged 40-60 years, who have varied dances in Itaqui city, Rio Grande do Sul, Brazil. Methodology: This descriptive study included 22 women, who an-swered a questionnaire containing questions about life style habits, nutritional status and satisfaction with body image. Anthropometric measurements including height, weight, circumference-s and skin folds were taken to assess the nutritional status. Results: From the evaluation of body satisfaction by the silhouettes range, 86.4% women were dissatisfied with their own image. In regard to the assessment of eating behavior and concerns about body shape, it was found that 90.9% women were free of dissatisfaction with their bodies. About food consumption, it was found a low water consumption and high consumption of red meat. Regarding the anthropometric status, 54.5% were normal weight, but all of them had a percentage of fat mass above normal. Conclusion: The sample of women studied has a profile concerned a-bout their health, but with a few erroneous eating habits, strongly influenced by cultural factors. Nutritional guidelines must be performed and the main-tenance of physical activity should be encouraged.
Keywords: Satisfação corporal; Avaliação nutricional; Comportamento alimentar; Dança; Climatério; Body image; Nutritional assessment; Dietary behavior; Dance; Climacteric; CNPQ::CIENCIAS DA SAUDE